The potential of spectral domain optical coherence tomography imaging based retinal biomarkers. Issue 1 (December 2017) - Phadikar, Prateep; Saxena, Sandeep; Ruia, Surabhi; Lai, Timothy; Meyer, Carsten; Eliott, Dean
Abstract Background Biomarker", a merged word of "biological marker", refers to a broad subcategory of medical signs that objectively indicate the state of health, and well-being of an individual. Biomarkers hold great promise for personalized medicine as information gained from diagnostic or progression markers can be used to tailor treatment to the individual for highly effective intervention in the disease process. Optical coherence tomography (OCT) has proved useful in identifying various biomarkers in ocular and systemic diseases. Main body Spectral domain optical coherence tomography imaging-based biomarkers provide a valuable tool for detecting the earlier stages of the disease, tracking progression, and monitoring treatment response. The aim of this review article is to analyze various OCT based imaging biomarkers and their potential to be considered as surrogate endpoints for diabetic retinopathy, age related macular degeneration, retinitis pigmentosa and vitreomacular interface disorder. These OCT based surrogate markers have been classified as retinal structural alterations (macular central subfield thickness and cube average thickness); retinal ultrastructural alterations (disruption of external limiting membrane and ellipsoid zone, thinning of retinal nerve fiber layer and ganglion cell layer); intraretinal microangiopathic changes; choroidal surrogate endpoints; and vitreoretinal interface endpoints. Conclusion OCT technology is changing very quickly and throughout this review there are some of the multiple possibilities that OCT based imaging biomarkers will be more useful in the near future for diagnosis, prognosticating disease progression and as endpoint in clinical trials.